First phase 1 double-blind, placebo-controlled, randomized rectal microbicide trial using UC781 gel with a novel index of ex vivo efficacy. - Peter A Anton; Terry Saunders; Julie Elliott; Elena Khanukhova; Robert Dennis; Amy Adler; Galen Cortina; Karen Tanner; John Boscardin; William G Cumberland; Ying Zhou; Ana Ventuneac; et al. (PLoS ONE, 2011)
Successful control of the HIV/AIDS pandemic requires reduction of HIV-1 transmission at sexually-exposed mucosae. No prevention studies of the higher-risk rectal compartment exist. We report the first-in-field Phase 1 trial of a rectally-applied, vaginally-formulated microbicide gel with the RT-inhibitor UC781 measuring clinical and mucosal safety, acceptability and plasma drug levels. A first-in-Phase 1 assessment of preliminary pharmacodynamics was included by measuring changes in ex vivo HIV-1 suppression in rectal biopsy tissue after exposure to product in vivo.HIV-1 seronegative, sexually-abstinent men and women (N = 36) were randomized in a double-blind, placebo-controlled trial comparing UC781 gel at two concentrations (0.1%, 0.25%) with placebo gel (1∶1∶1). Baseline, single-dose exposure and a separate, 7-day at-home dosing were assessed. Safety and acceptability were primary endpoints. Changes in colorectal mucosal markers and UC781 plasma drug levels were secondary endpoints; ex vivo biopsy infectibility was an ancillary endpoint.All 36 subjects enrolled completed the 7-14 week trial (100% retention) including 3 flexible sigmoidoscopies, each with 28 biopsies (14 at 10 cm; 14 at 30 cm). There were 81 Grade 1 adverse events (AEs) and 8 Grade 2; no Grade 3, 4 or procedure-related AEs were reported. Acceptability was high, including likelihood of future use. No changes in mucosal immunoinflammatory markers were identified. Plasma levels of UC781 were not detected. Ex vivo infection of biopsies using two titers of HIV-1(BaL) showed marked suppression of p24 in tissues exposed in vivo to 0.25% UC781; strong trends of suppression were seen with the lower 0.1% UC781 concentration.Single and 7-day topical rectal exposure to both concentrations of UC781 were safe with no significant AEs, high acceptability, no detected plasma drug levels and no significant mucosal changes. Ex vivo biopsy infections demonstrated marked suppression of HIV infectibility, identifying a potential early biomarker of efficacy. (Registered at ClinicalTrials.gov; #NCT00408538).